Răspuns :
a + b + c= 322 (1)
2×(a -13) = (b - 24) - 60
2a - 26 = b - 84⇒2a = b - 84 + 26⇒2a = b - 58
a = (b - 58)/2 (2)
(b - 24) + 10 = c - 50⇒b -14 = c-50⇒ c = b - 14 + 50
c = b + 36 (3)
In relatia (1) inlocuim relatiile (2) si (3)
(b-58)/2 + b + b + 36 = 322
Aducem la acelasi numitor
b - 58 + 2b + 2b + 72 = 644⇒ 5b +14 = 644
5b = 644 - 14⇒5b = 630
b = 126
dar a = (b - 58)/2 ⇒ a = (126 - 58)/2 = 68/2 = 34
iar c = b + 36 ⇒ c = 126 + 36 = 162
Deci a = 34, b = 126 si c = 162
2×(a -13) = (b - 24) - 60
2a - 26 = b - 84⇒2a = b - 84 + 26⇒2a = b - 58
a = (b - 58)/2 (2)
(b - 24) + 10 = c - 50⇒b -14 = c-50⇒ c = b - 14 + 50
c = b + 36 (3)
In relatia (1) inlocuim relatiile (2) si (3)
(b-58)/2 + b + b + 36 = 322
Aducem la acelasi numitor
b - 58 + 2b + 2b + 72 = 644⇒ 5b +14 = 644
5b = 644 - 14⇒5b = 630
b = 126
dar a = (b - 58)/2 ⇒ a = (126 - 58)/2 = 68/2 = 34
iar c = b + 36 ⇒ c = 126 + 36 = 162
Deci a = 34, b = 126 si c = 162